Adenocarcinoma arising in urinary bladder endocervicosis. Issue 2 (13th January 2016) - Nakaguro, Masato; Tsuzuki, Toyonori; Shimada, Satoko; Taki, Tetsuro; Tsuchiyama, Mari; Kitamura, Atsuko; Suzuki, Yasuhiko; Nakano, Yojiro; Ono, Kenzo
Abstract : Endocervicosis is a rare benign condition characterized by the presence of endocervical‐type mucinous glands. Urinary bladder endocervicosis forms an elevated lesion in the posterior wall of the urinary bladder and is sometimes misdiagnosed as a malignant tumor clinically and pathologically. Herein we describe the first case of adenocarcinoma arising in urinary bladder endocervicosis. The patient, a 58‐year‐old woman, presented with asymptomatic hematuria. Cystoscopy revealed a nodular mass measuring 4 cm in diameter in the posterior wall, and total cystectomy was performed. Histology revealed that the elevated lesion of the bladder wall was composed of haphazard proliferation of cystic glands lined by benign endocervical‐type epithelium. An adenocarcinoma arose at the center of this endocervicosis. Mucin histochemistry revealed the presence of sulfomucin in both the endocervicosis and adenocarcinoma components. Immunohistochemically, the endocervicosis was positive for cytokeratin (CK) 7, AE1/AE3, CAM5.2, HBME1, CA19‐9, and estrogen receptor (ER), and negative for CK20, CDX2, progesterone receptor (PR), MUC5AC, and β‐catenin. The adenocarcinoma showed similar immunohistochemical results, except for loss of ER expression and a slight increase in the ratio of Ki‐67‐positive cells. This case indicates that endocervicosis, known as a benign lesion, harbors the possibility of malignant transformation.